Concussion in University Level Sport: Knowledge and Awareness of Athletes and Coaches - Ben Kirk; Jamie N. Pugh; Rosanna Cousins; Shaun M. Phillips (MDPI AG, 2018)
Using a cross-sectional survey concussion knowledge was evaluated among forty university-level athletes (n = 20, rugby union players; n = 20, Gaelic football players) and eight experienced team coaches (n = 2, rugby union; n = 2, Gaelic football; n = 1, soccer; n = 1, hockey; n = 1, netball; n = 1, basketball). Levels of knowledge of concussion were high across all participants. Coaches had higher knowledge scores for almost all areas; however, there was evidence of important gaps even in this group. Knowledge was not sufficient in identifying concussion, and when it is safe to return to play following a concussion. Impaired knowledge of how to recognise a concussion, and misunderstanding the need for rest and rehabilitation before return to play presents a hazard to health from second impact and more catastrophic brain injury. We discuss reasons for these guideline misconceptions, and suggest that attitude issues on the significance of concussion may underlie a willingness to want to play with a concussion. This suggests the current education on sport-related concussion needs to be expanded for the appropriate management of university-level contact sports.